Monetary Policy Analysis Of Economic Stability and Growth in Facing Global Economic Challenges - Han Tantri Hardini; Waspodo Tjipto Subroto; Norida Canda Sakti (International Journal of Economics, Commerce, and Management, 2025)
This article analyzes monetary policy in the context of global economic challenges and its impact on economic stability and growth. In the era of globalization, dynamic changes in the global economy influence monetary policy which functions to maintain price stability and encourage growth. This research uses a qualitative research method with a literature review approach from international journals indexed by Scopus which were published in 2020-2024. The results of the research are that this research refers to several economic theories and previous studies which show that responsive monetary policy can contribute to controlling inflation and economic recovery. However, challenges such as market volatility, financial crises, and political instability are of major concern. This research concludes that the effectiveness of monetary policy varies between developed and developing countries, as well as the importance of collaboration between fiscal and monetary policy to achieve sustainable economic goals.